2021
DOI: 10.1002/fsh.10687
|View full text |Cite
|
Sign up to set email alerts
|

Celebrating 75 Years of Wisconsin’s Northern Highland Fishery Research Area: The Past, Present, and Future

Abstract: On June 20, 2021, the Northern Highland Fishery Research Area (NHFRA) celebrated its 75th anniversary of continuous fisheries population monitoring and compulsory angler creel census on five lakes in northern Wisconsin. In 1946, five lakes were designated as experimental fisheries research lakes and all anglers have been required to adhere to the compulsory creel census to record catch information. We review the history of the NHFRA, its role in evaluating experimental regulations, how data derived from the NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 57 publications
0
17
1
Order By: Relevance
“…Quist et al (2003) found that predation of age-0 Walleye by White Crappie was the most important mechanism explaining this negative interaction. In addition, for three CTWI lakes with no or limited Black Crappie populations and a long-time series of Walleye data, natural recruitment of Walleye has been consistent in the long term (Sass and Shaw 2018;Sass et al 2022b). Although our findings have only revealed negative associations between species and are unable to provide mechanisms, several explanations may exist to explain our results, including predator-prey interactions (Quist et al 2003), potential competition between adult Black Crappie and age-0 Walleye for zooplankton, lake surface area or morphometry limiting resource partitioning between the species, climate change and centrarchid abundances (Hansen et al 2015b(Hansen et al , 2017Rypel et al 2016), regulations favoring centrarchid abundance increases (Rypel 2015;Rypel et al 2016), the harvest-oriented nature of Walleye fisheries (Gaeta et al 2013;Hansen et al 2015b), and known depensation recruitment dynamics in Walleye .…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Quist et al (2003) found that predation of age-0 Walleye by White Crappie was the most important mechanism explaining this negative interaction. In addition, for three CTWI lakes with no or limited Black Crappie populations and a long-time series of Walleye data, natural recruitment of Walleye has been consistent in the long term (Sass and Shaw 2018;Sass et al 2022b). Although our findings have only revealed negative associations between species and are unable to provide mechanisms, several explanations may exist to explain our results, including predator-prey interactions (Quist et al 2003), potential competition between adult Black Crappie and age-0 Walleye for zooplankton, lake surface area or morphometry limiting resource partitioning between the species, climate change and centrarchid abundances (Hansen et al 2015b(Hansen et al , 2017Rypel et al 2016), regulations favoring centrarchid abundance increases (Rypel 2015;Rypel et al 2016), the harvest-oriented nature of Walleye fisheries (Gaeta et al 2013;Hansen et al 2015b), and known depensation recruitment dynamics in Walleye .…”
Section: Discussionmentioning
confidence: 77%
“…2015a, Sass et al. 2022a). To this point, attempts to rebalance fisheries in favor of Walleye have been mixed, likely due to the effort involved with whole‐lake fish removals (but see Sikora et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following our conceptualization of the potential influences of phenological variability on the ecology and evolution of north-temperate lake ecosystems, we present evidence of the influences of phenological variability from long-term datasets available from Escanaba Lake, a northtemperate lake in northern Wisconsin where ice phenology and biological data have been extensively monitored for the past 75 years (Sass et al 2021). We focus on altered ecosystem dynamics in early and late ice-off years and build the case that increasing variance in ice-off dates is likely to decrease ecological resilience and evolutionary rescue capacities in aquatic systems facing climatic change.…”
Section: Climate Change and Phenologymentioning
confidence: 99%